Approche de l’œuvre de Henri Meschonnic : « signifiance » et « infinitisation du sens » - Cohen, Monique Lise (Revue CMC Review, 2021)
In her last article for the Revue CMC Review, Monique Lise Cohen describes Henri Meschonnic’s immense work, which teaches us that the dualism of the signifiant/ signifié, which echoes the metaphysical dualism of the senses and intelligence, is at the heart of all dictatorial power. The Bible, on the other hand, in its original Hebrew, is not written according to this dualism. Its reading may lead to an “infinitisation du sens.” These questions open Meschonnic’s constant interrogation, on literature, on linguistics and philosophy, on translation, and on his own poetic writings.